Evaluation of Pharyngeal Background Mucosa in Patients with Superficial Hypopharyngeal Carcinoma. (17th March 2021) - Kimura, Yuki; Watanabe, Akihito; Shimizu, Yuichi; Goda, Kenichi; Ito, Suguru; Nishimura, Yusuke; Inoue, Masaki; Taniguchi, Masanobu
Abstract : Objectives/Hypothesis: Transoral surgery (TOS) has become increasingly popular for patients with superficial hypopharyngeal squamous cell carcinoma (SCC). However, the number of patients in whom metachronous multiple SCC of the head and neck (HNSCC) occurs has also increased. In this study, we investigated whether multiple lugol‐voiding lesions (LVLs) in the pharyngeal background mucosa observed during TOS would be a biomarker of metachronous HNSCC. Study Design: Retrospective study. Methods: We examined 362 patients who underwent TOS for superficial hypopharyngeal carcinoma. Endoscopic images were reviewed in a blinded fashion by two endoscopists. LVLs in the pharyngeal mucosa were graded as follows: A, no lesions; B, 1 to 4 lesions; and C, ≥5 lesions per endoscopic view. Results: Cumulative incidence curves of secondary HNSCC in the groups of grades A, B, and C revealed 3‐year incidence rates of 14.4%, 18.8%, and 29.3%, respectively ( P  = .001 for A vs. C and P  = .002 for B vs. C). Cumulative incidence curves of third HNSCC in the groups of grades A, B. and C revealed 5‐year incidence rates of 3.9%, 9.8%, and 19.6%, respectively ( P  = .001 for A vs. C and P  = .006 for B vs. C). Cumulative incidence curves of fourth HNSCC in the groups of grades A, B, and C revealed 7‐year incidence rates of 0%, 2.3%, and 13.2%, respectively ( P  = .025 for A vs. C and P  = .009 for B vs. C). Conclusions: Multiple LVLs in the pharyngeal mucosa increase the risk of development of metachronous multiple HNSCC. Level of Evidence: 3 (nonrandomized, controlled cohort/follow‐up study) Laryngoscope, 131:2036–2040, 2021